Perlindungan Hukum Data Pribadi Bagi Pelanggan Jasa Telekomunikasi Terkait Kewajiban Registrasi Kartu SIM - Mega Sonia Putri (Jurnal Cakrawala Hukum, 2018)
The government requires SIM card owners to register by submitting a Population Registration Number (NIK) and Family Card Number (KK) starting 31 October 2017 to 28 February 2018. This registration must be done for owners of new SIM Cards and old SIM Cards. For new SIM card owners who do not register, they cannot use the SIM card without activating with registration, while sanctions for old users will gradually get service blocking. The application of SIM Card registration is in accordance with the Regulation of the Minister of Communication and Information No. 14 of 2017 Amendment to the Regulation of the Minister of Communication and Information No. 12 of 2016. Until the enactment of this policy, the Government does not yet have a law that specifically protects personal data that has been submitted by the public and clear rules related to data management. The research results to date there is no protection of the personal data of the population in the SIM Card registration program because the regulations are still not comprehensive and are spread in several laws and regulations.How to cite item: Putri, M. (2018). Perlindungan Hukum Data Pribadi Bagi Pelanggan Jasa Telekomunikasi Terkait Kewajiban Registrasi Kartu SIM. Jurnal Cakrawala Hukum, 9(2), 195-203. doi:https://doi.org/10.26905/idjch.v9i2.2772